Analisis Resistansi Aliran Listrik pada Antena Ban untuk Mengetahui Efektivitas Antena sebagai Komponen Utama Sistem Pentanahan - Choirunnisa, Anis; Michael Siahaan, Paul; Putri Andini, Meilana (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
The development of electric vehicles (EV) has driven the tire industry to meet new standards related to electrical resistance, in order to ensure the effective discharge of static electricity to the ground. PT AMS continues to face challenges in maintaining the electrical resistance of tires within a stable range and in accordance with OEM customer specifications, which set a maximum limit of 10⁶ Ohms. This study aims to identify blocking points of electrical flow within the tire structure and to evaluate the effectiveness of the antenna as an additional grounding path. Experimental testing was conducted on three types of whole tires with different configurations using a Super Megohm Meter and an EKTRON machine. Data analysis included data sufficiency tests, normality test, homogeneity test, Welch ANOVA test, Games-Howell post hoc test, Welch T-Test, and effect size calculation (Cohen’s d). The results showed that the antenna significantly reduced resistance, especially when directly connected to the tread. These findings can serve as a reference for developing more conductive tire designs that meet EV industry standards.